Factors Affecting Housing Products Price in Jakarta Metropolitan Region - Rahadi, Raden Aswin; Wiryono, Sudarso Kaderi; Koesrindartoto, Deddy Priatmodjo; Syamwil, Indra Budiman (International Journal of Property Sciences (E-ISSN: 2229-8568), 2016)
This study addresses the issue of factors affecting housing products price in Indonesia, particularly in Jakarta Metropolitan Region. Based on a conceptual model conceived in the study, this preliminary study aims to validate the conceptual model and influencing factors for housing products price. Through a specially designed questionnaire, responses from housing consumers in late 2014 were used to analyse the current housing market products in Jakarta Metropolitan Region. Factors from the conceptual model and information about current housing products in Jakarta Metropolitan Region were combined to produce the questionnaire items. Eleven housing products from various areas and various segmentations in Jakarta Metropolitan Region were applied into the questionnaire. The findings suggested different preference factors for each of the housing development. They also confirm the current housing market conditions in Indonesia are facing overpriced situation. The responses indicate that consumers cannot afford the housing products offered at their current prices. This condition applies for most of the socio-economic and demographics attributes including the housing market segmentation, housing market locations and gender.